2009
DOI: 10.1073/pnas.0907926106
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial gut symbionts are tightly linked with the evolution of herbivory in ants

Abstract: Ants are a dominant feature of terrestrial ecosystems, yet we know little about the forces that drive their evolution. Recent findings illustrate that their diets range from herbivorous to predaceous, with ''herbivores'' feeding primarily on exudates from plants and sap-feeding insects. Persistence on these nitrogen-poor food sources raises the question of how ants obtain sufficient nutrition. To investigate the potential role of symbiotic microbes, we have surveyed 283 species from 18 of the 21 ant subfamilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
478
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(519 citation statements)
references
References 39 publications
32
478
7
2
Order By: Relevance
“…Based on the 16S rRNA gene sequence, the isolates shared a sequence similarity of 97.7 % with each other (based on 1552 bp) and a sequence similarity of 91.8 % with their closest cultivated neighbour, Opitutus terrae PB90-1 T (Chin et al, 2001). Additionally, strains CAG34 T and CV41 T shared sequence similarities with their closest environmental clones Fb-17 (obtained from C. rohweri; 99.8 % similarity) and 114a (obtained from C. varians; 99.7 % similarity), respectively (Russell et al, 2009).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Based on the 16S rRNA gene sequence, the isolates shared a sequence similarity of 97.7 % with each other (based on 1552 bp) and a sequence similarity of 91.8 % with their closest cultivated neighbour, Opitutus terrae PB90-1 T (Chin et al, 2001). Additionally, strains CAG34 T and CV41 T shared sequence similarities with their closest environmental clones Fb-17 (obtained from C. rohweri; 99.8 % similarity) and 114a (obtained from C. varians; 99.7 % similarity), respectively (Russell et al, 2009).…”
mentioning
confidence: 88%
“…By using PCR amplification and DNA sequencing techniques, previous studies have shown that members of the 'Verrucomicrobia' constitute part of a stable, autochthonous community of symbionts maintained in the guts of Cephalotes 'turtle' ants (Anderson et al, 2012;Kautz et al, 2013;Russell et al, 2009). These symbionts are protected by a proventricular filter (Lanan et al, 2016), remain stable in laboratory-reared colonies and likely coevolved with their hosts (Sanders et al, 2014).…”
mentioning
confidence: 99%
“…A preliminary assembly of the Wolbachia sequences is hosted on antgenomes.org. The 16S sequence of the γ-proteobacterium showed 98.4% identity with an Enterobacteriaceae of a C. obscurior sample from Florida, USA (voucher RA0330, GenBank: GQ275143), detected during a survey of ant-associated bacteria (Russell et al, 2009).…”
Section: Resultsmentioning
confidence: 97%
“…The 16S sequence of an unknown Enterobacteriaceae isolated from C. obscurior was previously published (Russell et al, 2009), but the specificity and functionality of this association had not been addressed. Here, we describe it as 'Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Across such a phylogenetic scale, related hosts indeed often harbor similar microbes (see, for example, Jones et al, 2013), as do those with similar diets (Ley et al, 2008). Well documented in the mammals and in several insects, specific symbioses related to particular trophic habits are widely argued to reflect the importance of bacteria in host dietary utilization (see, for example, Ley et al, 2008;Russell et al, 2009). Empirical and metagenomic evidence clearly indicate such an importance (Feldhaar et al, 2007;Douglas, 2009;Muegge et al, 2011).…”
Section: The Functional Implications Of Variable Gut Communitiesmentioning
confidence: 99%